2015
DOI: 10.1093/jjco/hyv019
|View full text |Cite
|
Sign up to set email alerts
|

Tumour multifocality and grade predict intravesical recurrence after nephroureterectomy in patients with upper urinary tract urothelial carcinoma without a history of bladder cancer

Abstract: Objective: Patients with upper urinary tract urothelial carcinoma (UUT-UC) without a history of bladder cancer have a different natural history of intravesical recurrence after nephroureterectomy compared with those with a history of bladder cancer. The aim of this study was to identify predictive factors for post-operative intravesical recurrence in patients with non-metastatic upper urinary tract-localized urothelial carcinoma without a history of bladder cancer and who were not taking medication during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…When these two papers are considered together, we found that the results have an internal consistency: Low-grade tumour was associated with a low level of Ki-67 expression as shown in our study. However, Narukawa et al (22) found that high-grade tumour predicted intravesical recurrence after nephroureterectomy in UTUC patients. Another Chinese scholar found there was no relationship between Ki-67 and bladder cancer recurrence in 88 UTUC patients, because some patients who receive neoadjuvant chemotherapy were included and patients with concomitant/previous bladder cancers were not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…When these two papers are considered together, we found that the results have an internal consistency: Low-grade tumour was associated with a low level of Ki-67 expression as shown in our study. However, Narukawa et al (22) found that high-grade tumour predicted intravesical recurrence after nephroureterectomy in UTUC patients. Another Chinese scholar found there was no relationship between Ki-67 and bladder cancer recurrence in 88 UTUC patients, because some patients who receive neoadjuvant chemotherapy were included and patients with concomitant/previous bladder cancers were not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This study considered 3‐year DFS as a prognostic outcome because the intravesical recurrence after RNU was approximately 20%‐50% within 1‐1.5 years, and the OS or CSS was estimated at 3‐ or 5‐years . Therefore, the 3‐year DFS comprised local recurrence, cancer‐specific, and non–cancer‐specific death, but not intravesical recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rarity of UTUC and difficulty of long-term follow-up because of poor prognosis, this study's strengths are that it provides a useful prediction model in Asian UTUC patients who underwent RNU and considers diverse parameters, whereas the only two existing Asian prediction models did not have similarly large cohorts for the development and validation sets, but instead used small cohorts to evaluate IVRFS and CSS. 6,11 This study considered 3-year DFS as a prognostic outcome 14 because the intravesical recurrence after RNU was approximately 20%-50% within 1-1.5 years, 22,23 and the OS or CSS was estimated at 3-or 5-years. 2,6,10 Therefore, the 3-year DFS comprised local recurrence, cancer-specific, and non-cancer-specific death, but not intravesical recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies assessed patients from within Korea [22], 3 from China [24,25], and 8 from Japan [26][27][28][29][30][31][32][33]. Only one study was an RCT [30], 4 were casecontrol [22,27,31,32] studies, and the others were retrospective cohort searches [24-26, 28, 29, 33]. The size of the studies varied from 36 to 754, with a total number of 2942 patients.…”
Section: Methods Of Systematic Selection Of Relevant Publicationsmentioning
confidence: 99%
“…The study was considered relevant if it met the inclusion criteria. Finally, 11 eligible articles [22,[24][25][26][27][28][29][30][31][32][33]] from 2010 to 2016 was selected. The primary information the investigators recorded included author, publication year, region, study type, recruitment period, number of patients, baseline characteristics (mean age and sex, etc.…”
Section: Data Extractionmentioning
confidence: 99%